Nana in the city - Castillo, Lauren (Clarion Books, Houghton Mifflin Harcourt, 2014)
A young boy is frightened by how busy and noisy the city is when he goes there to visit his Nana, but she makes him a fancy red cape that keeps him from being scared as she shows him how wonderful a place it is.